Pengaruh LKPD Inkuiri Terstruktur Berbantuan Quick Response Code terhadap Peningkatan Kemampuan Literasi Sains Peserta Didik Kelas VIII SMP Negeri 25 Makassar - Deviani L.; Nurhayani H. Muhiddin; Muhammad Aqil Rusli (Celebes Science Education, 2023)
This study aims to determine 1) Improvement of science literacy skills of VIII grade students of SMP Negeri 25 Makassar who are taught using structured inquiry LKPD assisted by Quick Response Code, 2) Improvement of science literacy skills of VIII grade students of SMP Negeri 25 Makassar who were taught using conventional LKPD, 3) The effect of using structured inquiry based Quick Response Code on improving the science literacy skills of students in class VIII SMP Negeri 25 Makassar. This research is a Quasi-Experiment using the Nonequivalent Control Group Design. The population of all students in class VIII SMP Negeri 25 Makassar consisting of 10 classes totalling 267 students, the sample was selected by purposive sampling with 2 classes, namely class VIII 8 as the control class with a total of 23 students and class VIII 10 as the experimental class with a total of 23 students. Data collection was done by giving Pretest and Posttest. Data were analysed with descriptive statistics and inferential statistics. The results of the analysis showed that   1) The improvement in the science literacy skills of students who use structured inquiry LKPD assisted by Quick Response Code with an average N-Gain score of 0.60 is in the medium category, 2) Increasing the science literacy skills of students who use conventional LKPD with an average N-Gain score of 0.19 is in the low category, 3) There is an effect of using structured inquiry LKPD assisted by Quick Response Code on improving the science literacy skills of students in class VIII SMP Negeri 25 Makassar with the results of hypothesis testing, where tcount = 7.05> ttable = 1.68.